Brain anatomy of the marine tardigrade actinarctus doryphorus (arthrotardigrada). (11th October 2013) - Persson, Dennis K.; Halberg, Kenneth A.; Jørgensen, Aslak; Møbjerg, Nadja; Kristensen, Reinhardt M.
ABSTRACT Knowledge of tardigrade brain structure is important for resolving the phylogenetic relationships of Tardigrada. Here, we present new insight into the morphology of the brain in a marine arthrotardigrade, Actinarctus doryphorus, based on transmission electron microscopy, supported by scanning electron microscopy, conventional light microscopy as well as confocal laser scanning microscopy. Arthrotardigrades contain a large number of plesiomorphic characters and likely represent ancestral tardigrades. They often have segmented body outlines and each trunk segment, with its paired set of legs, may have up to five sensory appendages. Noticeably, the head carries numerous cephalic appendages that are structurally equivalent to the sensory appendages of the trunk segments. Our data reveal that the brain of A. doryphorus is partitioned into three paired lobes, and that these lobes exhibit a more pronounced separation as compared to that of eutardigrades. The first brain lobe in A. doryphorus is located anteriodorsally, with the second lobe just below it in an anterioventral position. Both of these two paired lobes are located anterior to the buccal tube. The third pair of brain lobes are situated posterioventrally to the first two lobes, and flank the buccal tube. In addition, A. doryphorus possesses a subpharyngeal ganglion, which is connected with the first of the four ventral trunk ganglia. The first and second brain lobes in A. doryphorus innervate the clavae and cirri of the head. The innervations of these structures indicate a homology between, respectively, the clavae and cirri of A. doryphorus and the temporalia and papilla cephalica of eutardigrades. The third brain lobes innervate the buccal lamella and the stylets as described for eutardigrades. Collectively, these findings suggest that the head region of extant tardigrades is the result of cephalization of multiple segments. Our results on the brain anatomy of Actinarctus doryphorus support the monophyly of Panarthropoda. J. Morphol. 275:173–190, 2014. © 2013 Wiley Periodicals, Inc.